Implementation of a Spiral-Hybrid Arabic Language Curriculum: Integration of KMA 2019 and Pesantren Traditions in Madrasah Aliyah - M Bakiruddin; Asep Maulana; Abdur Rosid; Mokhammad Miftakhul Huda (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
This study aims to explore the practical implementation of the national Arabic language curriculum based on the Decree of the Minister of Religious Affairs (KMA) Number 183 of 2019 in the context of pesantren-based madrasahs, particularly at MA Miftahul Ulum Al-Azizah. Using a qualitative descriptive method, data were collected through classroom observation, interviews with teachers, and analysis of curriculum documentation. The results of the study show that (1) Madrasah Aliyah Miftahul Ulum Al-Azizah formally adopts the national curriculum and uses the textbook “Ayo Fasih Berbahasa Arab” (Let's Be Fluent in Arabic), but its implementation is adjusted due to the institution's ban on the use of digital devices. (2) To overcome these limitations, teachers apply a spiral-Hybrid model that integrates the modern curriculum with classical Islamic texts (turats) such as Al-Jurumiyyah and Alfiyyah Ibnu Malik. This model not only overcomes technological limitations but also deepens students' syntactic and morphological understanding, thereby promoting more in-depth linguistic competence. Based on the research results, it can be concluded that curriculum adaptation based on local pedagogical traditions can be an effective alternative in educational environments with limited resources. This study contributes to the discourse on contextual curriculum development in Arabic language teaching in religious educational environments.